Leadership Style Practices of Principals and Organizational Commitment Profile of Employees of Dioceasan Catholic Schools - Magallanes, Vivian M.; Dioso, Dexter Paul D. (Philippine Social Science Journal, 2020)
The principals play a vital role in the success of the schools. The leadership style practices of the principals can have a wedge on the commitment of employees. Keeping committed teachers is a challenge faced by educational leaders. Hence, the paper describes the extent of leadership style practices and employees’ organizational commitment profile in Antique Diocesan Catholic Schools (ADCS) during the school year 2019-2020. Likewise, it explores the significant difference in principals’ leadership style practices as perceived by the employees when grouped according to demographics. Also, it determines the relationship that exists in the extent of leadership style practices and organizational commitment profile of employees.